Flam Valley TMF Pond, 40 Years of Activity and Still Going. Issue 5 (September 2019) - Popescu, Catalin; Sarghiuta, Radu; Iiev, Sorin
Abstract: Flam Valley is a bauxite residue Tailings Management Facility (TMF) valley pond, operating since 1971, located in Romania, just a few meters away from the Danube Delta protected area. Since then, it has been serving Alum Tulcea alumina producing plant through the different stages of its development. Conceived as a frontal tailings dam, Flam Valley is located in a nonpermanent torrential stream in a very sensitive environmental protected area. Up to 2006 tailings slurry with 15-20% solids were pumped by pipeline in the TMF, in accordance with the old technology. After the EU directives enforcement in 2005 the plant had to stop all activity until the whole process was upgraded, consequently the TMF was upgraded with the structural frontal dam being reinforced, water diversions constructed, some areas of the residual storage area were ecologically restored and the deposition became a dry stacking process by tailing placement, thus transforming it into a new TMF and avoiding the consequences that would have derived from the relocation of the TMF. The presented aspects are aimed at generally portraying the evolution, incidents, the tailing dam behavior and prospects of capacity enlargement for Flam Valley TMF.